Equalizing access: affirmative action in higher education in India, United States, and South Africa - Zoya Hasan, Ed; Nussbaum, Martha C, Ed (Oxford University Press, 2012)
Papers presented at a conference on 'Affirmative action in higher education in India, United States, and South Africa', held at New Delhi in March 2008.